Petechiae in non-fatal strangulation: Prevalence, predictors and time-dependent detectability in forensic assessment - Babigian, Julia; Berti, Luca; Oesterhelweg, Lars; Amadasi, Alberto (Forensic science international, 2026)
Petechiae are a key yet inconsistently observed finding following non-fatal strangulation, and their detection is influenced by both anatomical location and time since the event. This variability complicates forensic evaluation. This retrospective cohort study analysed 541 adult cases assessed at the Violence Protection Ambulatory of Charité Berlin between 2017 and 2023. The presence of petechiae was evaluated according to location and time interval to examination. Associations with clinical symptoms and external signs were examined using logistic regression, generalised estimating equations, and receiver operating characteristic (ROC) analysis. Petechiae were observed in 10 % of cases (54/541) and were significantly associated with shorter intervals between the event and examination (mean: 26 h vs. 61 h, p < 0.001), with a cut-off of 41.5 h (AUC 0.73 (95 % CI 0.6739–0.7953)). Early detectability was most common in the conjunctiva, while petechiae in the posterior ear region persisted longer (OR = 27.65). Clinical symptoms such as dyspnoea, hoarseness, and dysphagia were also associated with the presence of petechiae. A two-item risk score combining dyspnoea and absence of external skin findings achieved an AUC of 0.72. These findings suggest that petechiae are both time- and site-dependent and that clinical symptoms and external signs may support early identification. The proposed score provides a practical tool to aid forensic assessment in cases of suspected strangulation. •Petechiae are key but time-sensitive markers of non-fatal strangulation injuries.•Early forensic exams increase petechiae detection, aiding accurate strangulation diagnosis.•Dyspnoea and skin injuries strongly predict petechiae presence in strangulation cases.•Women, especially young adults, represent the majority of strangulation and petechiae cases.•Developed risk score supports structured strangulation assessment and early detection.